Riffaterre's Semiotic Study of the Qasidah Ya Badrotim in Maulid Ad-Diba'i Tradition - Nurul Khadroh Khadroh; Penny Respati Yurisa (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to explore the comprehensive meaning and symbolism of the qasidah